Oral Health Problems of Diabetic Patients - Mahbub, S; Ferdouse, S; Zaman, MH (Bangladesh Journal of Dental Research & Education, 2013)
The worldwide estimated prevalence of Diabetes Mellitus is 4.6% in 20-79 year aged population. In 1985, an estimated 30 million people worldwide had diabetes. The World Health Organization warns diabetes will reach epidemic with 300 million by 2025.The prevalence of diabetes is the highest in developed countries but developing countries are expected to have the largest increase in next decade.1 Uncontrolled diabetes leads to soreness, ulcers, infections and tooth decay and decrease oral health status.3 Objective: To assess oral health status among the diabetic patients in dental department of BIRDEM. Methods: It was a cross sectional type of descriptive study conducted among 110 patients for 6 months period. Data were collected using questionnaire and oral examination checklist. SPSS software was used for data analysis. Results: Males were 61.8% and 32.7% were in 40-50 years age group, post-graduate educated were 47.3%, 40.9% were employed in job and monthly family income was taka >20000. The highest 31.8% were diabetic for 3-10 years and 47.3% were under control. Regularly 85.5% patients checked blood sugar and followed the advice. Oral hypoglycemic was taken by 60.9% patients and followed diabetic diet 76.4%. Dental health problems developed in 44.5% diabetes patients, 41.8% developed Gum Swelling, 22.7% Bleeding during brushing teeth, 16.4% Bad breath, 16.4% had Pain and 2.7% having loosening their teeth. Both grade 3 gingivitis and grade 2 periodontitis were found in 34.5%. Maximum 48.2% visited dental surgeon. Conclusion: Regular dental care is particularly important for people with diabetes. DOI: http://dx.doi.org/10.3329/bjdre.v3i2.16610 Bangladesh Journal of Dental Research & Education Vol.3(2) 2013: 29-35